2022
DOI: 10.5194/acp-2022-88
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric Oxidation Mechanism and Kinetics of Indole Initiated by ·OH and ·Cl: A Computational Study

Abstract: Abstract. The atmospheric chemistry of organic nitrogen compounds (ONCs) is of great importance for understanding the formation of carcinogenic nitrosamines and ONC oxidation products might influence atmospheric aerosol particle formation and growth. Indole is a polyfunctional heterocyclic secondary amine with global emission quantity almost equivalent to that of trimethylamine, the amine with the highest atmospheric emission. However, the atmospheric chemistry of indole remains unclear. Herein, the reactions … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…121 However, Xue et al found that cOH addition was the dominant pathway for the reaction of cOH with indole which is a polyfunctional heterocyclic secondary amine. 122 Amines are also attacked by O 3 . Gai et al believed that amines might react with O 3 through the electrophilic reaction mechanism.…”
Section: Oxidation Mechanisms 321 the Initial Step Of Oxidation React...mentioning
confidence: 99%
See 4 more Smart Citations
“…121 However, Xue et al found that cOH addition was the dominant pathway for the reaction of cOH with indole which is a polyfunctional heterocyclic secondary amine. 122 Amines are also attacked by O 3 . Gai et al believed that amines might react with O 3 through the electrophilic reaction mechanism.…”
Section: Oxidation Mechanisms 321 the Initial Step Of Oxidation React...mentioning
confidence: 99%
“…There are some experimental and computational studies exploring its initial steps. [122][123][124][125][127][128][129] In 2003, Rudić et al rst revealed that hydrogen-abstraction occurred with roughly equal probability from both the carbon and nitrogen sites of MA in the reaction of cCl with MA through isotope experiments. 127 Sz} ucs et al also found that the hydrogen-abstraction of carbon and nitrogen sites of MA was exothermic low-barrier, but the substitution reactions were endothermic high-barrier using an accurate composite ab initio approach.…”
Section: Oxidation Mechanisms 321 the Initial Step Of Oxidation React...mentioning
confidence: 99%
See 3 more Smart Citations